Quality of Long-Term Care in an LTC Outlier: Insights from the Greek Case - Lalioti, Varvara (Berry) (Socialinė teorija, empirija, politika ir praktika, 2026)
Population ageing, within an evolving socioeconomic and technological landscape, has brought renewed attention to the quality of Long-Term Care (LTC), a multidimensional concept encompassing, inter alia, regulatory design, monitoring capacity, service delivery structures, user engagement and workforce conditions. Yet, substantial cross-national variation in the definition and operationalisation of ‘LTC quality’ – including the absence of any definition in some national legislations – hinders comparative understanding and system-wide improvement. Greece represents a particularly instructive case. Despite having one of the fastest-ageing populations in Europe and the EU’s lowest public expenditure on LTC, the LTC sector in this country remains characterised by fragmented governance, minimal public investment, heavy reliance on informal and migrant carers, and the near absence of palliative care, dementia services and quality-assurance mechanisms. Against this background, this exploratory article examines how key stakeholders conceptualise LTC quality, the challenges they identify, and the pathways they consider necessary for improvement. Drawing on 15 semi-structured interviews with academics/LTC policy experts, public officials, senior administrators/managers of LTC units, as well as formal and informal carers, the qualitative thematic analysis utilised identifies six interlinked themes: conceptual ambiguities and legislative gaps; the absence of comprehensive quality standards; data deficiencies and weak monitoring infrastructures; minimal quality-assurance mechanisms; limited user involvement and persistent unmet needs; and workforce constraints that undermine LTC quality. These themes cluster around the three dimensions that dominate international debates on LTC quality: conceptual and regulatory foundations; monitoring and accountability; and care experience and delivery. The findings reveal severe weaknesses but also highlight opportunities for reform, including the establishment of measurable quality standards, development of interoperable data systems, and construction of a coherent quality-assurance architecture. The analysis ultimately suggests that improving LTC quality requires not only a legislative reform, but also sustained political commitment, meaningful stakeholder engagement and everyday practices grounded in the lived realities of care.